Influence of physical activity on problematic smartphone use in medical students: mediating effects of social anxiety and the moderating role of gender - Song, Yanhong; Zhang, Guofeng; Liu, Ningning; Zhang, Yaqi; Zhai, Jinghua; Niu, Xingmeng; Liu, Yan (Frontiers in Psychology, 2024)
Objective: This study investigates the mediating role of social anxiety in the relationship between physical activity and problematic smartphone use among college students, and examines the moderating role of gender within this model.: From April to May 2023, a survey was conducted involving 2905 undergraduate students from various medical schools in Shandong, China. Participants completed the Physical Activity Rating Scale (PARS-3), Mobile Phone Addiction Tendency Scale for College Students (MPATS), and the Social Anxiety Scale (IAS). Descriptive statistics, correlation analysis, and hierarchical regression analysis and other methods were employed to explore the relationships between the variables. The mediating effect of social anxiety on physical activity and mobile phone addiction was assessed using the bootstrapping method, while the moderating role of gender on social anxiety and mobile phone addiction was evaluated using the PROCESS macro's model 14.The findings revealed that the scores of problematic smartphone use among medical students was 44.00 (35.00, 50.00), physical activity score was 16.00 (8.00, 32.00) and social anxiety score was 45.00 (42.00, 52.00). Physical activity was significantly and negatively correlated with both problematic smartphone use and social anxiety (P<0.001), and social anxiety was significantly and positively correlated with problematic smartphone use (P<0.001). Social anxiety partially mediated the effect between physical activity and problematic smartphone use (β=-0.04, 95%CI=-0.05 to -0.02), with a mediation effect proportion of 57.14%. Sex played a moderating role between social anxiety and problematic smartphone use (β=-0.30, 95%CI=-0.39 to -0.21).: Physical activity influences problematic smartphone use among medical students both directly and indirectly through social anxiety. Sex significantly moderates the influence of social anxiety on problematic smartphone use, highlighting the need for gender-specific interventions in this demographic.